Describing vocal performance of Portuguese cantadeiras of Alto Minho - Araújo, Pedro André Guerreiro Martins de (2015)
Portugal has strong musical traditions, which have been perpetrated by decades through folkloristic activities. In folk groups from Alto Minho (north of Portugal), folk singing is mostly performed by cantadeiras, amateur female solo singers who learn this style orally. Their vocal characteristics are distinctive when compared with other regions of the country; however, deep understanding of these vocal practices is still missing. The present work aims at studying Alto Minho cantadeira’s vocal performance in a multidimensional perspective, envisioning social, cultural and physiological understanding of this musical style. Thus, qualitative and quantitative data analyses were carried out, to: (i) describe current performance practices, (ii) explore existent perceptions about most relevant voice features in this region, (iii) investigate physiological and acoustic properties of this style, and (iv) compare this style of singing with other non-classical singing styles of other countries. Dataset gathered involved: 78 groups whose members were telephone interviewed, 13 directors who were asked to fill in a questionnaire on performance practices, 1 cantadeira in a pilot study, 16 cantadeiras in preliminary voice recordings, 77 folk group members in listening tests, and 10 cantadeiras in multichannel recordings, including audio, ELG, air flow and intra-oral pressure signals. Data were analysed through thematic content analysis, descriptive and inferential statistics, hierarchical principal components, and multivariate linear regression models. Most representative voices have a high pitched and loud voice, with a bright timbre, predominance of chest register without excessive effort, and good text intelligibility with regional accent. High representativeness levels were obtained by few cantadeiras; these sing with high levels of subglottal pressure and vocal fold contact quotient, predominance of high spectrum energy and vocal loudness, corroborating indications of prevalence of pressed phonation. These vocal characteristics resemble belting in musical theatre and share similarities with country (USA) and ojikanje (Croatia) singing. Strategies that may contribute to the preservation of this type of singing and the vocal health of current cantadeiras are discussed, pointing at the direction of continuous education among folk groups, following practices that are already adopted elsewhere in Europe.